An evaluation of America's security transfers during the Cold War - Cooley, Jason (2024)
As the United States participates in a military conflict inside a developing country, it is common for instability to surface in many locations. At first, U.S. officials attempted to cope with this issue by keeping combat troops in a nation for decades. Over the course of time, though, they began to have local forces assume the responsibilities of American soldiers. To ascertain whether this transferal policy is an effective tool for decreasing instability, it is imperative to evaluate prior missions in nations such as South Korea and South Vietnam. While looking at the literatures about the Korean and Vietnam Wars, it becomes evident that most of the assessments of the transfers in South Korea and South Vietnam lack degrees of success and failure. These works also do not contain convincing explanations for the outcomes in South Korea and South Vietnam. To properly explain the result of a security transfer, it is necessary to devote a substantial amount of attention to many determinants and the interplay between them. In their explanations, researchers overlook key factors that contributed to the outcomes in South Korea and South Vietnam. The main objective of the thesis is to contribute to the literatures regarding the Korean and Vietnam conflicts. Through the utilization of levels of success and failure from policy studies publications, it will be possible to conduct sophisticated appraisals of the transfers within South Korea and South Vietnam. There will then be an opportunity to offer persuasive explanations for the outcomes that emerged in these developing countries. The thesis uses principal-agent concepts as a framework to guide the empirical data and help a reader see the influence of the determinants that were not taken into account in prior works. This study will also be of interest to parties outside of academia. Given its prior behavior, it is safe to say that the U.S. will conduct more transfers in the developing world in the years ahead. Consequently, policymakers should be more familiar with the circumstances that are conducive to successful operations. The content from the explanations for the outcomes in South Korea and South Vietnam will be used to construct a set of conditions which is likely to lead to productive initiatives in conventional conflicts.